2007
DOI: 10.1177/0021886306295295
|View full text |Cite
|
Sign up to set email alerts
|

Readiness for Organizational Change

Abstract: Using a systematic item-development framework as a guide (i.e., item development, questionnaire administration, item reduction, scale evaluation, and replication), this article discusses the development and evaluation of an instrument that can be used to gauge readiness for organizational change at an individual level. In all, more than 900 organizational members from the public and private sector participated in the different phases of study, with the questionnaire being tested in two separate organizations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
311
0
26

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 815 publications
(450 citation statements)
references
References 37 publications
7
311
0
26
Order By: Relevance
“…Furthermore, it helps employees change their conceptual as well as the emotional viewpoints on their current status quo (Buchanan et al, 2005;Lai & Ong, 2010). In support of this, Holt et al (2007) suggested a more comprehensive approach including structured communication process to staff on compelling reasons for the intended change, the enablers and intended outcome. When adequate communication is deployed to employees, they will be more likely to understand and will resonate the idea of the insecurity of the current status and further open their mind.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, it helps employees change their conceptual as well as the emotional viewpoints on their current status quo (Buchanan et al, 2005;Lai & Ong, 2010). In support of this, Holt et al (2007) suggested a more comprehensive approach including structured communication process to staff on compelling reasons for the intended change, the enablers and intended outcome. When adequate communication is deployed to employees, they will be more likely to understand and will resonate the idea of the insecurity of the current status and further open their mind.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Skala yang digunakan dalam penelitian ini terdiri dari tiga macam. (1) Skala kesiapan individu untuk berubah yang mengacu pada teori Holt et al (2007) …”
Section: Instrumen Penelitianunclassified
“…Pemimpin organisasi, dalam hal ini perlu untuk menilai kesiapan perubahan sebelum mereka memperkenalkan perubahan itu sendiri, agar mereka mampu mengidentifikasi kesenjangan antara inisiatif mengenai perubahan yang mereka ajukan dengan harapan yang dimiliki pegawai (Holt, Armenakis, Feild, & Harris, 2007). Hasil penilaian ini diharapkan menjadi panduan bagi organisasi untuk menentukan cara dan langkah terbaik dalam menerapkan perubahan.…”
unclassified
“…The researchers have used synonym terms for the learning organizations including (knowing organization, thinking organization, and purposeful organization) (Lozano, 2015;Holt, and Harris, 2007). The learning organization is defined by a set of definitions, but the definition that serves the objectives of this study is the following: (Is the organization that works to create, exchange and transfer knowledge, according to the reciprocal, participatory and complementary relationships which leading to modify its behavior, for starting to collective learning , development of the existing thinking patterns, creation of new thinking patterns and development of creativity to achieve adaptation, change and development, as well as achieving the collective aspirations and strategic objectives) (Bryan, 2009) .…”
Section: Learning Organizationmentioning
confidence: 99%